2004
DOI: 10.1007/s00213-003-1719-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported psychopathological symptoms in recreational ecstasy (MDMA) users are mainly associated with regular cannabis use: further evidence from a combined cross-sectional/longitudinal investigation

Abstract: The present findings suggest that self-reported psychopathology in ecstasy users is predominantly attributable to concomitant use of cannabis. Abstinence from cannabis and not ecstasy seems to be a reliable predictor for remission of psychological complaints in ecstasy users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
71
2
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 32 publications
10
71
2
1
Order By: Relevance
“…Related to these findings, self-report personality measures have revealed elevated impulsivity and/or novelty/sensation seeking among MDMA users (e.g., Curran and Verheyden, 2003;Butler and Montgomery, 2004;Daumann et al, 2004;Gerra et al, 1998Gerra et al, , 2000Gerra et al, , 2002Morgan et al, 2002;Schifano, 2000;Tuchtenhagen et al, 2000;Verkes et al, 2001), which may also impact decision making. Although MDMA use may have led to these elevations (Morgan, 1998;Parrott et al, 2000), impulsivity and novelty/sensation seeking could be pre-existing traits among drug users (Allen et al, 1998;Conway et al, 2002;Mitchell, 1999), perhaps contributing to drug use initiation (Daumann et al, 2004;Dughiero et al, 2001).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Related to these findings, self-report personality measures have revealed elevated impulsivity and/or novelty/sensation seeking among MDMA users (e.g., Curran and Verheyden, 2003;Butler and Montgomery, 2004;Daumann et al, 2004;Gerra et al, 1998Gerra et al, , 2000Gerra et al, , 2002Morgan et al, 2002;Schifano, 2000;Tuchtenhagen et al, 2000;Verkes et al, 2001), which may also impact decision making. Although MDMA use may have led to these elevations (Morgan, 1998;Parrott et al, 2000), impulsivity and novelty/sensation seeking could be pre-existing traits among drug users (Allen et al, 1998;Conway et al, 2002;Mitchell, 1999), perhaps contributing to drug use initiation (Daumann et al, 2004;Dughiero et al, 2001).…”
Section: Introductionmentioning
confidence: 94%
“…Although MDMA use may have led to these elevations (Morgan, 1998;Parrott et al, 2000), impulsivity and novelty/sensation seeking could be pre-existing traits among drug users (Allen et al, 1998;Conway et al, 2002;Mitchell, 1999), perhaps contributing to drug use initiation (Daumann et al, 2004;Dughiero et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies reported increased levels of depression (Sumnall and Cole, 2005), impulsivity (Morgan, 1998;Parrott et al, 2000;Tuchtenhagen et al, 2000;Daumann et al, 2001Daumann et al, , 2004bBond et al, 2004;Butler and Montgomery, 2004), and sensation/novelty seeking (Gerra et al, 1998;Tuchtenhagen et al, 2000;Schifano, 2000;Dughiero et al, 2001) in ecstasy users, although it is unclear whether these associations reflect a causal relationship, that is whether ecstasy use causes changes in mood, impulsivity, and sensation seeking or whether depression, impulsivity, and sensation seeking increase the probability of (heavy) ecstasy use (see also De Win et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Parrott et al (2001) found that the heavier the polydrug use alongside ecstasy the higher the level of self-reported psychological symptoms. Other studies have also shown that elevated psychopathology in ecstasy users appears to be associated more with polydrug use (Medina and Shear, 2007), and in some cases specifically cannabis rather than ecstasy (Daumann et al, 2001;Morgan et al, 2002;Rosier and Sahakian, 2004;Daumann et al, 2004). A possible combination effect of ecstasy and cannabis use is also supported by recent findings from Milani et al (2005), who reported that heavy cannabis use appeared to exacerbate psychobiological problems in ecstasy users, and Lamers et al (2006) who found that individuals who used both ecstasy and cannabis reported more symptoms of anxiety and depression than non-drug users and cannabis only users.…”
Section: Introductionmentioning
confidence: 99%
“…A range of measures have been used to record such psychobiological problems, including clinical measures such as the Symptom Checklist-90 (Parrott, Sisk and Turner, 2000;Parrott et al, 2001;Dugherio et al, 2001;Milani et al 2004), the Symptom Checklist-90-Revised (Daumann et al, 2001(Daumann et al, & 2004Morgan et al, 2002;Thomasius et al, 2006), and specific measures of depression (MacInnes et al, 2001;de Win et al, 2006;Lamers et al, 2006) and anxiety (Lamers et al, 2006). These studies have shown that ecstasy users often demonstrate higher levels of psychopathology than non-ecstasy user control groups.…”
Section: Introductionmentioning
confidence: 99%